Testing the environmental Kuznets Curve hypothesis at the sector level: Evidence from PNARDL for OECD countries - Muratoğlu, Yusuf; Songur, Mehmet; Uğurlu, Erginbay; Şanlı, Devran (Frontiers in Energy Research, 2024)
Since the contribution of economic sectors to GDP is heterogeneous, they also contribute differently to CO2 emissions and environmental degradation. In this regard, it is crucial to examine the Environmental Kuznets Curve (EKC) hypothesis at the sectoral level. Nevertheless, despite the extensive research conducted on the Environmental Kuznets Curve (EKC) hypothesis, significant gaps remain in the existing literature, particularly at the sectoral level. This study makes a novel contribution to the existing literature on the environmental EKC hypothesis by examining its validity across four distinct sectors: agriculture, industry, manufacturing, and services. Additionally, it makes a second contribution to the literature by examining the effect of energy consumption on CO2 asymmetrically, employing a novel panel non-linear ARDL (PNARDL) method. The study employs annual data from 38 OECD countries, spanning the period from 1990 to 2022. The findings demonstrate that the EKC hypothesis is valid for sectors other than the industrial sector and for the economy as a whole. The turning point of the Kuznets Curve for the total economy is estimated as 29250 GDP per capita. The PNARDL model's error correction term (ec) is negative and significant. However, the magnitude of the term suggests that the system will return to long-term equilibrium after approximately 2.87 years following any shock. Asymmetric effects are valid for four sectors. Moreover, the empirical results clearly show that energy consumption has asymmetric effects on emissions in both the long and short run. Positive and negative shocks in energy consumption increase CO2 emissions in OECD economies in the long run. It has been determined that agriculture is the sector that causes the most environmental degradation by increasing CO2 emissions. This situation highlights the limited availability of productive capital equipment and renewable sources in the agricultural sector, even in OECD countries. As a result, the findings show that there is a different relationship between each sector's GDP and CO2 emissions. It is important for policymakers to formulate sector-specific policies to reduce CO2 emissions while fostering GDP growth.